X-Ray Topography - Hartwig, J. B.; Hartwig, J.; S. N., Aqida (Elsevier, 2016)
X-ray topography is a nondestructive technique to characterize strain and visualize inhomogeneties, imperfections, and distortions in crystals. This article presents X-ray topography fundamentals, basic technique, and simulation. In principle, the topographic information produced by diffracted X-ray beam when the Bragg condition is satisfied. Among the basic extended beam methods are integrated wave and plane wave topography. The integrated wave method includes white beam X-ray topography which is the Laue technique with low divergent, powerful, and broad incident beam. The advent of synchrotron radiation topography permits a fast and detailed study of defects in crystalline materials.